BENTUK PERTUNJUKAN TARI PILIN SALAPAN DI KENAGARIAN AIR BANGIS KECAMATAN SUNGAI BEREMAS KABUPATEN PASAMAN BARAT - Febriani, Lili; Fitri, Hasminda (Universitas Negeri Padang, 2026)
This study aims to describe and analyse the form of the Pilin Salapan Dance Performance in Kenagarian Air Bangis, Sungai Beremas District, West Pasaman Regency. This type of research is qualitative with a descriptive method. It uses primary and secondary data, with the main researcher being the researcher themselves, supported by instruments such as writing tools and a camera. Data collection techniques are conducted through literature study, observation, interviews, and documentation. The steps of data analysis are data collection into classifications, data analysis, data interpretation and drawing conclusions. The research results show that the Pilin Salapan Dance performances are often displayed within the community. The Pilin Salapan Dance is frequently performed at events organised by the local community such as weddings, festivals, birthdays in West Pasaman and the welcoming of the West Pasaman regent, performed at the request of the West Pasaman tourism office and at competition events.